Tumor microenvironment features decipher the outperformance of neoadjuvant immunochemotherapy over chemotherapy in resectable non-small cell lung cancer - Cai, Wenhan; Jing, Miao; Gu, Yajun; Bei, Ting; Zhao, Xiaochen; Chen, Shiqing; Wen, Jiaxin; Gao, Jie; Wu, Chongchong; Xue, Zhiqiang (Frontiers in Immunology, 2022)
This study evaluated the efficacy of neoadjuvant immunochemotherapy (Io+Chemo) versus chemotherapy alone (Chemo) in resectable non–small cell lung cancer (NSCLC) in a real-world setting. The association of tumor immune microenvironment (TIME) with pathologic response to different neoadjuvant therapies was also explored.Stage I−III NSCLC patients who received Io+Chemo or Chemo alone followed by surgery were included in the study. Tumor tissues collected during surgery were subjected to TIME evaluation using multiplex immunohistochemistry to measure immune cell subsets, including T cells, B cells, NK cells, and macrophages. Fifty-five patients were included, including 24 treated with neoadjuvant Io+Chemo and 31 with Chemo alone. Io+Chemo induced significantly higher major pathologic response (MPR) (75.0% vs. 38.7%, P = 0.0133) and numerically better pathologic complete response (pCR) (33.3% vs. 12.9%, P = 0.1013) than Chemo. Compared with tumors with Chemo, tumors with Io+Chemo demonstrated a significantly higher ratio of M1 macrophage density in the tumor to that in the stroma (P = 0.0446), more abundant CD8+ cells in the stroma (P = 0.0335), and fewer PD-L1+CD68+ cells in both tumor and stroma. pCR/MPR patients displayed significantly higher density of CD3+, CD3+CD4+, CD20+, CD56 bright cell subsets and more tertiary lymphoid structures and significantly lower density of PD-L1+CD68+ and CD3+CD4+Foxp3+cells in the tumor or stroma. This study favored neoadjuvant Io+Chemo over Chemo and revealed the TIME features underlying the outperformance of Io+Chemo over Chemo.